2006
DOI: 10.1139/x06-197
|View full text |Cite
|
Sign up to set email alerts
|

Twenty year responses of white spruce to mechanical site preparation and early chemical release in the boreal region of northeastern British Columbia

Abstract: The effects of six mechanical site preparation treatments, two stock-type treatments, and early chemical release on survival and growth of planted white spruce (Picea glauca (Moench) Voss) were studied in the BWBSmw1 biogeoclimatic zone of northeastern British Columbia. After 20 years, spruce height and diameter were larger in all mounding treatments than in the control. Early results suggested better spruce performance on large than small mounds, but after 20 years, growth was equally good on small mounds as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 41 publications
5
28
1
Order By: Relevance
“…Increases in volume ranged from 5% to 11 800% in the Pacific Northwest, from 15% to 5800% in the southeast, and from 50% to 5500% in northern forests. These results and those from more recent longer-term work (~20 years post treatment) in British Columbia (e.g., Boateng et al 2006Boateng et al , 2009 concur with those of Stewart et al (1984) who documented that virtually every study where competing vegetation has been effectively controlled resulted in increased survival and/or growth of conifers. The exception to these results is where other factors (e.g., harsh climate, insects, disease) that are not remediated The Forestry Chronicle Downloaded from pubs.cif-ifc.org by 34.216.127.252 on 05/12/18…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Increases in volume ranged from 5% to 11 800% in the Pacific Northwest, from 15% to 5800% in the southeast, and from 50% to 5500% in northern forests. These results and those from more recent longer-term work (~20 years post treatment) in British Columbia (e.g., Boateng et al 2006Boateng et al , 2009 concur with those of Stewart et al (1984) who documented that virtually every study where competing vegetation has been effectively controlled resulted in increased survival and/or growth of conifers. The exception to these results is where other factors (e.g., harsh climate, insects, disease) that are not remediated The Forestry Chronicle Downloaded from pubs.cif-ifc.org by 34.216.127.252 on 05/12/18…”
Section: Introductionsupporting
confidence: 75%
“…Hearnden et al (1992) further observed that such plantations may not provide the same quantity of conifer fibre as the original stands due to competition from aspen (Hearnden et al 1992). Since that time, results of several experimental studies have been published for northern conifers (e.g., Boateng et al 2006Boateng et al , 2009. examined 23 of the oldest (i.e., ≥10 years of post-treatment growth measurements) conifer release studies in North America that included control (untreated) plots.…”
Section: Introductionmentioning
confidence: 99%
“…Research and operational experience have shown that fairly rigorous vegetation management is required to counter the natural propensity of upland boreal sites to regenerate aspen following harvest (Wood and von Althen 1993, Cole et al 2003, Pitt and Bell 2005, Boateng et al 2006 and that unintentional, intimate mixedwoods are often the result of conventional conifer regeneration efforts (Navratil et al 1991, Pitt et al 2004a2004b, Pitt andBell 2005). In 2000, we worked with a coalition of forest industry partners to formulate and test a practical regeneration strategy for a singlecohort, intimate mixture of spruce and aspen that would capitalize on the natural propensity of these sites to regenerate aspen following harvest.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, soil scarification is recognized to increase soil temperature and moisture, and favour organic matter mineralization especially in boreal ecosystems (Prévost 1992). Seedling growth and survival are enhanced, as biotic and abiotic conditions are positively modified (Grossnickle and Heikurinen 1989), which can lead to increased timber supply in the long-term (Boateng et al 2006). Under non-optimal conditions, seedlings suffer various stresses that can negatively affect their physiology and growth (Margolis and Brand 1990;Grossnickle 2005Grossnickle , 2012.…”
Section: Introductionmentioning
confidence: 99%